Hemostasis in sickle cell disease - Nawal Khalil Ibrahim1, Awatif Radhi 2, Nehaya Mnahi Al-Aubody3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Sickle cell disease results in a significant morbidity and mortality related to intra-vascular thrombosis. This study is an attempt to improve our understanding the role of hypercoagulability in the pathogenesis of sickle cell disease. A case group of 20 asymptomatic sickle cell adult patients in a steady-state were compared with a control group of 20 normal adult people , both groups aged (18-50) year and from both sex, to evaluate the process of hemostasis. An investigation has been done for both groups including estimation of hemoglobin, platelets count, bleeding time and clotting time. There is a highly significant increase in the number of platelets with (P<0.01) together with a highly significant decrease in bleeding time with (P<0.01) for a case group in comparison with a control group. There is no significant difference of clotting time between both groups. That may suggest that the platelets aggregation formation activity is significantly increase in patients with sickle cell disease in a steady-state.